Assessment of NT-ProBNP and Troponin T in Sera of Iraqi Patients with Renal Failure - Nour Saeed Hassan (Journal of Global Pharma Technology, 2019)
Background: Patients with renal failure have high risk of cardiovascular disease which is a leading cause of morbidity and mortality among these patients. This study aimed to evaluate the effect of renal failure on the cardiac system by measuring the following markers (NT-ProBNP and Troponin T) and compared with healthy subjects. Method: This study consists of a total (90) subjects, among them (60) patients with end stage renal failure and (30) healthy persons that served as control group. This study has been carried out in AL-Yarmok Teaching Hospital and AL-Karama Teaching Hospital in Baghdad for the period from February 2017 till May 2017. Serum (NT-ProBNP and Troponin T) were done by enzyme-linked immunosorbent assay (ELISA). Results: this study showed an increasing significant in the levels of NT-Pro BNP and Troponin T for patients with renal failure compared with control group. Conclusion: Renal failure was affected on cardiac system as the cardiac markers (NT-ProBNP &troponin T) levels were increased significant. Keywords: NT-ProBNP, Troponin T, Renal failure.